From the young Turks to Kemalists: Links and discontinuities - Dunham, Erica (AUC Knowledge Fountain, 2017)
While current scholarship often points to a direct link between the ideology of Young Turks and the Kemalists, a closer analysis indicates there are many breaks in this link. This thesis analyzes the main influences on the Young Turk movement and the emergence and rise to power of the Kemalist movement, highlighting points of difference in the two movements' ideologies and practices. Although the Young Turk movement influenced the Kemalist movement in the early years of the Turkish Republic, this thesis seeks to highlight the differences and discontinuities that existed between them. While many ideas from the Young Turk movement did carry over to the Kemalist movement, the extent and form of some of ideas differed. Scholars acknowledge that the Young Turk movement included numerous factions, whose ideology and practices differed greatly. Noticeable divides existed within the Young Turk movement, particularly between the movement's leadership and its radical faction, the garbcilar. It is the ideology of the Young Turk leadership's inner circle, the Central Committee, which is often compared with that of the Kemalists. However, many of the notable individuals who went on to lead and contribute to the ideology of the Kemalist movement were actually associated with the garbcilar and did not play a role in the Central Committee. In support of this argument, I will point to how the garbcilar, rather than the CUP central leadership, provided much of the inspiration for the radical aspects of Kemalist ideology and policies that prevailed in the early twentieth century. To be clear, this thesis does not seek to discredit or disprove current scholarship, but rather to present the relationship between the ideology of the Young Turk and Kemalist movements through a different lens. By tracing the ideological links of the Kemalists back to the Young Turk movement, this thesis will highlight the limits of ideological continuity. In doing so, it will contribute to the existing scholarly literature on Ottoman and early Turkish thought in the late nineteenth and early twentieth centuries.